2013
DOI: 10.1016/j.jpainsymman.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Growth of an Academic Palliative Medicine Program: Patient Encounters and Clinical Burden

Abstract: Objectives Our aim is to describe the growth and staffing structure of a palliative care program at a comprehensive cancer center. Methods During fiscal years (FYs) ending in 2000 through 2010, we recorded all billed palliative care consultations and follow-ups. In order to determine the yearly clinical burden per physician, advanced practice nurse (APN) and physician assistant (PA), we calculated the mean number of patient encounters per clinical full time equivalents. Increase in absolute number of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…Thus, a business model that allows for space and staff expansion will be necessary to accommodate the increase in patient referrals without compromising patient care and adequate number of follow-up visits for previously established patients. We have previously shown that to keep up with increased growth in referral and workload, there needs to be appropriate and timely recruitment of PC clinicians [26]. In FY 2012, we added a second outpatient clinic and increased outpatient palliative clinic physicians from 2 to 3, and again, based on the continued growth, expanded the clinic to 3 locations within the cancer center and increased clinic physicians to 4 per day in FY 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a business model that allows for space and staff expansion will be necessary to accommodate the increase in patient referrals without compromising patient care and adequate number of follow-up visits for previously established patients. We have previously shown that to keep up with increased growth in referral and workload, there needs to be appropriate and timely recruitment of PC clinicians [26]. In FY 2012, we added a second outpatient clinic and increased outpatient palliative clinic physicians from 2 to 3, and again, based on the continued growth, expanded the clinic to 3 locations within the cancer center and increased clinic physicians to 4 per day in FY 2014.…”
Section: Discussionmentioning
confidence: 99%
“…This PC consultation rate (%) for each FY was calculated as the number of inpatient PC consultations divided by the total number of admissions for the DoCM and Internal Medicine service. Second, we also used our previously reported metric of the ratio of inpatient consultations to the average number of inpatient operational beds per FY [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Several centers have published their experience with freestanding outpatient clinics . In most cases, these clinics have begun as single, one‐half–day clinics per week and have grown quickly with increasing demand . Large cancer centers, such as The University of Texas MD Anderson Cancer Center and the Princess Margaret Cancer Center, have clinics that operate daily and offer both booked and urgent same‐day appointments.…”
Section: Innovative Models Of Care Deliverymentioning
confidence: 99%
“…This finding was not surprising, and it speaks to the rapid uptake of palliative care services by referring clinicians, as has been found in adult palliative care programs. 42 Based on our anecdotal experience providing advice to a wide variety of PPC programs, when programs start, they typically have few staff, yet they are soon inundated with more consultations than can be appropriately managed, leading to allocation of new resources to increase team size. The problem of increasing referrals necessitating more specialist staff has led to a call, in the realm of adult palliative care, for increasing the pipeline of palliative care fellowships and greater generalist palliative care training for all hospital staff so as to offload the demand on specialists.…”
Section: Figurementioning
confidence: 99%